DAMPAK PENGGUNAAN GADGET TERHADAP PERKEMBANGAN NILAI AGAMA DAN MORAL ANAK USIA DINI DI TK ISLAM BAKTI 53 TANJUNG HARAPAN PULAU MAINAN DHARMASRAYA - Deby Habja Musdalifa; Ahmad Lahmi; Rahmi Rahmi (Universitas Labuhanbatu, 2022)
The use of gadgets today is no longer in adults, but all age levels have become accustomed to using this device. This reality has an impact on its users. Therefore, this study is intended to uncover the impact of gadget use on early childhood morals. Research is carried out with a qualitative approach. The results of the research obtained are: first, the use of gadgets in early childhood at TK Islam Bakti 53 Tanjung Harapan Dharmasraya Toy Island which consists of class A group 6 children and class B group 18 children, namely the duration of use of early childhood gadgets, namely 1 to 4 hours / day. with content that is often accessed, including youtube, tiktok, mobile lagend, freefire, toca kichen, etc.Second, the use of gadgets in early childhood has a negative impact, namely in the form of low achievement of indicators of the development of early childhood religious values as stated in Permendikbud No. 146 of 2014, especially in the 5th indicator, namely carrying out worship. Third, the use of gadgets in early childhood also has a negative impact on the development of early childhood immorality, namely in the form of low achievement of indicators of early childhood moral development as stated in PP No. 58 of 2009, especially on indicators of accustomed to mutual respect and indicators of doing useful deeds.